Student Consumptive Behavior in Online Shopping Through E-Commerce Shopee - Tiara Agustin; Ila Navilah (Cirebon International Journal of Economics and Business, 2023)
Consumptive behavior is a person's action in buying goods excessively, the purchase is in accordance with the wishes, not in accordance with the needs. The purpose of this study is to find out the factors that influence student consumptive behavior in online shopping through e-commerce shopee and strategies implemented by students to minimize consumptive behavior in online shopping through e-commerce shopee. In this study using qualitative methods, the research population was students majoring in Sharia Economics, Faculty of Islamic Economics and Business, IAIN Syekh Nurjati Cirebon Academic Year 2022/2023, totaling 136 students, with a sample of 10 respondents and the sampling technique used purposive sampling. The data sources used in this study are primary and secondary data sources. Data collection techniques were carried out through interviews and observation, and data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate that more students behave consumptively. This consumptive behavior is caused by several factors, namely perceptions about online shopping, discount factors, online shopping because it follows fashion trends, online shopping to maintain appearance, and online shopping because it is influenced by friendship groups. The strategy used by students to minimize consumptive behavior is by making a list of needs or priorities, managing finances properly, getting into the habit of saving, not using online loans such as shopee paylaters, having to be able to control or control yourself, and not frequently opening the shopee application.